Theoretical aspects of studying financial ecosystems - A. V. Savtsova; A. I. Khakirov (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. The financial ecosystems of the Russian model serve as an example of successful cooperation between financial institutions and revolutionary digital technologies. In just a few years, the largest banks in Russia have been able to fully adapt to completely new economic realities due to an unconventional way of expanding their influence on financial and non-financial markets. The uniqueness of Russian financial ecosystems makes it necessary to conduct a comprehensive study of this phenomenon in order to understand the essence of the new business model, which brings certain risks not only for the banking sector, but also for the entire economy of the country.Goal. The study aims to systematize the available data on financial ecosystems, propose approaches to their definition and introduce a classification that would allow a more detailed study of each example of Russian ecosystems.Materials and methods. The study is based on the analysis of Russian scientific literature on the topic of financial ecosystems. In the course of the study, statistical data on financial indicators of large financial ecosystems and consolidated values of indicators for the entire banking sector of the Russian Federation were studied. The report for public consultations of the Bank of Russia was studied.Results and discussion. The paper presents the results of systematizing the position of Russian scholars on the issue of defining financial ecosystems. The criteria for classifying financial ecosystems are proposed.Conclusion. The results of the study show that the problem of defining and classifying financial ecosystems is acute, so this phenomenon should be systematically studied in different areas of research, starting with the formation of the conceptual apparatus and ending with mathematical modelling of the possible consequences of uncontrolled ecosystem development.